(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Background: Polytrauma is the result of high energy trauma and presents itself as damage to multiple systems of the body. Fractures frequently exist. The presence of femoral and pelvic fractures is alarming and presents a great challenge to trauma surgeons. There are two different schools of thought regarding the timing of definitive surgical fixation in polytrauma patient i.e. early total care and the damage control orthopaedics. Each approach has its merits and demerits. The clinical status of the patient determines the appropriate orthopaedic approach, which should aim at the survival of the patient. Objective: To assess the best possible orthopaedic approach in a patient with blunt multiple injuries. Patients and Methods: This is a retrospective study that included 36 patients of multiple trauma with associated fractures of femur or pelvis during the period 1433-35 at Prince Mutaib Bin Abdul Aziz Hospital Sakaka, Aljouf, Saudi Arabia. The patients’ age was 20-60 years. The spectrum of injuries varied. All patients had deranged one or more vital functions. Road traffic accident was the main cause of multiple injuries in our series. Early total care (ETC) or damage control orthopaedics policy was followed. We tried to find out the best possible orthopaedic approach by studying the incidence of acute respiratory distress syndrome (ARDS), multiple organs dysfunction syndrome (MODS), pneumonia, pulmonary embolism, death rate as well as the length of ICU and hospital stay. Postoperatively patients received antibiotics and low molecular weight heparin (clexane 40 mg S/C). The effect of early total care/damage control orthopaedics (DCO) on surgical fixation was also studied. Bilateral femoral fractures were excluded from the study. They represent separate entity with different prognosis. Results: The mean patients’ age was 38.61±10.28 (range 20-60 years). We followed Pape classification to group the patients on the basis of their clinical status. There was derangement of one or more vital functions along with fracture of femur or pelvis. We targeted to achieve control of bleeding, haemodynamics and ventilation. Subsequently the clinical status of the patient guided us to follow the policy of ETC or DCO. In our series ETC was carried out on 33 patients after resuscitation. Seven of them deteriorated after surgical stabilization of femur/pelvis. Early total care was effective in 26 stable patients (72.3%). Damage control orthopaedics was followed in 3 unstable patients (8.4%). Seven borderline cases in our study developed ARDS after ETC (19.4%). The mean follow-up period was 10.08±1.11 (range 9-12 months). Bony union was achieved in all cases. Conclusion: The results of our series of multiple trauma patients indicate that the best orthopaedic approach can not be predetermined definitely at the time of presentation of patient to emergency room. Early total care is indicated in a stable patient within 24-48 hours after injury. Damage control orthopaedics is adopted in unstable patients preferably between 5th-10th days. Effectiveness of resuscitation plays important role. Keywords: Multiple trauma, Femoral/pelvis fracture, Early total care, damage control orthopaedics